Persepsi Mahasiswa Calon Guru Matematika Terhadap Soal Pembuktian Matematika - Hakim, Fauziah; Sartika Arifin; Aprisal, Aprisal (Mandalika Mathematics and Educations Journal, 2025)
This study aims to investigate the perceptions of prospective mathematics teachers regarding proof-based learning from four aspects: conceptual understanding, the relevance of proofs in teaching, the challenges faced, and confidence in teaching proofs. Data were collected using a questionnaire completed by 65 students of the Mathematics Education Study Program at Unsulbar who took the Modern Algebra course in the 2024/2025 academic year. The results show that the majority of students recognize the importance of proofs for deepening mathematical understanding and as a reasoning tool. They also view proofs as relevant material for teaching in secondary schools. However, students reported difficulties in understanding the language and steps of proofs, as well as limitations in guidance. Additionally, the students' confidence level in teaching proofs was moderate, with many feeling pedagogically unprepared. These findings indicate the need for structured proof materials, intensive guidance, and specialized pedagogical training to enhance students’ abilities and confidence in teaching proofs. The implementation of hands-on practical experiences in secondary schools is also strongly recommended to support the readiness of prospective teachers.